Student preparedness characteristics important for clinical learning: perspectives of supervisors from medicine, pharmacy and nursing - Hasini Banneheke; Vishna Devi Nadarajah; Srinivasan Ramamurthy; Afshan Sumera; Sneha Ravindranath; Kamalan Jeevaratnam; Benny Efendie; Leela Chellamuthu; Purushotham Krishnappa; Ray Peterson (BMC Medical Education, 2017)
Abstract Background Student perspectives of clinical preparedness have been studied in the literature, but the viewpoint of supervisors is limited. Hence, the aim was to examine the perspective of supervisors on the characteristics of health professional students important for preparedness for clinical learning. Methods This was a descriptive, questionnaire-based, cross-sectional study conducted at three higher education institutions in Malaysia. A previously published questionnaire with 62 characteristics was adopted with modifications after pre-testing. Descriptive analysis was completed for the demographic data. The sample was grouped based on health profession, clinical practice experience and teaching experience for further analysis. Non-parametric Kruskal-Wallis test was selected to evaluate differences in mean ranks to assess the null hypothesis that the medians are equal across the groups. Kruskal-Wallis post-hoc pair wise comparison was performed on samples with significant differences across samples. Results The sample was comprised of 173 supervisors from medicine (55, 32%), pharmacy (84, 48%) and nursing (34, 20%). The majority (63%) of the supervisors were currently in professional practice. A high percentage (40%) of supervisors had less than 4 years of teaching experience. The highest theme ratings were for willingness (6.00) and professionalism (5.90). There was a significant difference (p < 0.05) in the medians, among medicine, pharmacy and nursing professional speciality for willingness (5.70, 6.00 and 6.00), professionalism (5.70, 5.90 and 6.15), communication and interaction (5.42, 5.67 and 6.00), personal attributes (5.42, 5.71 and 6.02) and the professional and interpersonal skills (5.50, 5.63 and 6.00) themes. Post-hoc analysis showed a significant difference (p < 0.05) between medicine and nursing groups in the willingness (5.70 and 6.00), professionalism (5.70 and 6.15) and personal attributes (5.42 and 6.02) themes. Supervisors who are currently in practice had given high ratings compared to other groups. There were no significant differences observed within groups with different level of teaching experiences. Conclusions All supervisors rated professionalism and willingness as the most important characteristics followed by personal attributes. Further strengthening learning opportunities related to these characteristics in the curriculum may improve the students’ preparedness in clinical learning.